Autoavaliação nas instituições de ensino superior de Ceará sob a égide do Sistema Nacional da Educação Superior - SINAES. - Lima, Cláudia Ibiapina (2010)
This work is stimulated by reflection on with IES of Ceará began to develop the process of self-assessment within the institutional framework. This concern leads us to study that aims to diagnose the state of knowledge and acceptance of higher education institutions (IESs) Ceará about building self-assessment in force, as initial and essential step, as established by Law No. 10.861 (SINAES). Currently the theme institutional assessment is widely discussed within the institutions of higher education, because the search for institutional efficiency and improving the quality of education. With the institutionalization of Law No. 10.861 of 14 April 2004 (SINAES), the institutional assessment is now guided by fundamental principles, we can highlight the whole, recognizing the diversity of the system and the continuing evaluation process in institutional framework with the participation of all segments of the academic community. In this context, the question of evaluation of higher education is really new. To establish the main differences between current procedures and prior to SINAES walked the path a methodological descriptive ex post facto, using qualitative and quantitative approaches. In the bibliographic and documentary found that the current SINAES is the result of a long history of institutional assessment programs developed for the Brazilian higher education in the period 1980 to 2004. In the current evaluation system of higher education, the difference is the institutional self-assessment, conducted by the Commission for assessment (CPA), consisting of the leader of the IES. The investigative research, through questionnaires, had the background of the IES Ceará, we check the level of knowledge of participants about the stages of self-assessment, commitment and acceptance of those involved in the evaluation process and the description of the difficulties and facilities identified by the coordinators of CPAs in the implementation of self-assessment within the IES.Com the results obtained in this study, we found that AI programs developed in Brazil for higher education had regulatory purposes and summative functions. With the institutionalization of SINAES significant advances have occurred in relation to the role of evaluation that has to be formative, emancipator and a regulatory overview. We found that the AI has to have a transforming character, building the integration of internal evaluation (self assessment) and external. Before the diagnosis, we found that higher education institutions comply with the cearenses the common law, that is, the bureaucratic aspect. Therefore, there is a long way to go by the institution for assimilation of the new culture of evaluation established by the evaluation system SINAES. Considering these findings, the paper presents some recommendations on an alternative proposal to reflect the self assessment introduced by SINAES within the IES Ceará.